INABILITY TO USE ACTIVE VOCABULARY IN SPEECH - Alimova Dildora Komiljon qizi,; Eshonkulova Rukhshona Ilhom kizi, (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Many people who learn a foreign language face the same problem: they know many words, but they cannot remember them when they need to talk. This is called "passive vocabulary." We understand these words easily in books or movies, but in a real conversation, we often use only very simple language. This happens because we feel nervous and do not have much time to think while speaking. This article explains why this happens and how we can practice more to start using all the words we know in our speech.